2015
DOI: 10.1182/blood.v126.23.4040.4040
|View full text |Cite
|
Sign up to set email alerts
|

Enestpath: A Phase III Study to Assess the Effect of Nilotinib Treatment Duration on Treatment-Free Remission (TFR) in Chronic Phase-Chronic Myeloid Leukemia (CP-CML) Patients (pts) Previously Treated with Imatinib: Interim Analysis from the First Year of Induction Phase

Abstract: Background Tyrosine kinase inhibitors (TKIs) are the standard of care for pts with CP-CML. Current recommendation is to continue TKI therapy indefinitely but previous studies indicate that pts with deep and sustained molecular responses (MRs) on imatinib (IM) may achieve long-lasting TFR. Nilotinib (NIL) at 300mg BID induces higher rates of deep MRs compared to IM and high dose NIL (400mg BID) enables a substantial proportion of pts who do not obtain MR4 (BCR-ABL1IS £ 0.01%) or MR4.5 (BCR-ABL1IS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The median age of patients in TARGET‐RMC was similar to those in a recent CML‐CP French cross‐sectional epidemiological survey (62 years) (Etienne et al , ) and were older than those in other second line nilotinib clinical studies (Kantarjian et al , ; Nicolini et al , ; Hughes et al , ; Gora‐Tybor et al , ; Kuo et al , ; Rea et al , ; Miyamura et al , ).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The median age of patients in TARGET‐RMC was similar to those in a recent CML‐CP French cross‐sectional epidemiological survey (62 years) (Etienne et al , ) and were older than those in other second line nilotinib clinical studies (Kantarjian et al , ; Nicolini et al , ; Hughes et al , ; Gora‐Tybor et al , ; Kuo et al , ; Rea et al , ; Miyamura et al , ).…”
Section: Discussionsupporting
confidence: 68%
“…Of note, the indication of nilotinib in first line treatment was approved in 2011 based on a total daily dose of 600 mg. In addition, and to our knowledge, there are only two recent studies documenting results with a 600 mg/day dose of nilotinib post‐imatinib treatment: the ENRICH study (Cortes et al , ) and the ENESTPath study (Rea et al , ), neither of which included imatinib‐resistant patients.…”
Section: Discussionmentioning
confidence: 99%
“…Whether improvement of results will be observed in patients treated with second-generation TKIs as firstor second-line therapy is currently being evaluated in ongoing discontinuation trials. 23,30,31 Indeed, discontinuation of dasatinib as second-line therapy in the DADI (Discontinuation of Dasatinib in Patients With Chronic Myeloid Leukaemia Who Have Maintained Deep Molecular Response for Longer Than 1 Year) trial was associated with a probability of treatment-free remission of 49% at 6 months and 48% at 12 months. 31 Several randomized clinical studies have demonstrated that second-generation TKIs as firstor second-line therapies are associated with higher rates and faster deep molecular responses when compared with IM.…”
Section: Discussionmentioning
confidence: 99%
“…11,[19][20][21][22][23][24][25][26] Most of these trials included patients treated with imatinib. 11,[19][20][21][22][23]26,27 Other studies involve patients treated with 2 nd generation TKIs nilotinib 6,22,24,[26][27][28][29][30] and dasatinib. 22.24-27,31 Table 1 summarizes the results of different TFR trials.…”
Section: Treatment Free Remissionmentioning
confidence: 99%